Study of reactions of Nε-(carboxymethyl) lysine with o-benzoquinones by cyclic voltammetry. (1st March 2020) - Li, Yuting; Huang, Qiaoling; Yu, Xiangying; Liu, Yujia; Li, Lin; Li, Bing; Zhang, Xia; Chen, Sui; Liu, Zhan; Zhao, Xianglong; Ma, Jingjing
Highlights: Electron-donating substituent weakens quinones Nε-(carboxymethyl)lysine trapping. Electron-withdrawing substituent enhances quinones Nε-(carboxymethyl)lysine trapping. Steric hindrance of o -benzoquinone affects its reaction with Nε-(carboxymethyl)lysine. Abstract: The reaction of N ε -(carboxymethyl) lysine (CML) with eight kinds of non-flavonoid o -benzoquinones and five kinds of flavonoid o -benzoquinones were investigated by cyclic voltammetry at pH 5.0, 7.0 and 8.0 and scan rate of 10, 50 and 100 mV/s. The reactivity of o -benzoquinones towards CML is weakened by the electron-donating substituent and strengthened by the electron-withdrawing substituent on the o -benzoquinone rings. The steric hindrance of the substituents on o -benzoquinone rings also weakens the quinone reactivity. Reaction of 4-methylbenzoquinone with CML (38.0 ± 1.3%) was found to be faster than that with l -lysine (31.3 ± 1.5%) and Nα-acetyl-l -lysine (14.5 ± 0.1%) but slower than that with l -cysteine (≥100.0%) and Nα-acetyl-l -cysteine (≥100.0%) at pH 7.0 and scan rate of 10 mV/s. Products obtained by the reaction of CML with o -benzoquinones were found to include a CML-quinone adduct according to the cyclic voltammetry and UPLC-QTOF-MS/MS analysis.